Analisis perbandingan kinerja keuangan bank syariah dan bank konvensional terhadap keputusan investasi periode tahun 2017-2021 - Hertina, Dede; Rahmah, Maghfirah Aulia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the comparison of the financial performance of Conventional Banks and Islamic Banks to investment decisions. This research was conducted on conventional banking institutions and Islamic banking listed on the Indonesia Stock Exchange in 2017-2021. The population used is all banks in Indonesia. Meanwhile, the sample used was 3 conventional banks and 3 Islamic banks in Indonesia. This method of analysis uses a descriptive method with a quantitative approach, the data used are secondary data obtained from financial statements. Data analysis techniques are carried out with the testing stage of descriptive analysis and independent sample t-test analysis. The results showed that there was no significant difference between the financial performance of Conventional Banks and Islamic Banks in the 2017-2021 period.